University entrepreneurial development program as incubation process - Rapiei, Shaha Bahar (2010)
This paper reviews the concept of University-based Incubator in Malaysian university. Entrepreneurial development process in the university can be implemented through adaptation of incubator concept or through incubation process. This incubation process can ignite the entrepreneurship spirit and nurturing different business idea into viable business. During the incubation, student will get accurate information and knowledge in entrepreneurship and business aspect through seminar and course that attended and practical hands-on start-up experiences. This can enhance student motivation and competency. Hence, it is important to the University used incubator concept for entrepreneurial development program.